HUBUNGAN KONSEP DIRI AKADEMIK DENGAN PRESTASI AKADEMIK - Saifullah Saifullah (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2015)
This study aims to test empirically the relationship between academic self concept and studentâ€™s academic achievement of SMK â€œAâ€ Banyuputih. The hypothesis proposed that there is a positive relationship between academic self concept and studentâ€™s academic achievement. Participants of the study comprised 150 of SMK students. The research data obtained from academic self concept scale and students report. Data analyzed use product moment correlation technique. The results showed that the data obtained correlation values rxy = 0,325 with p = 0,001. This is indicate that there was a positive relationship between academic self concept and studentâ€™s academic achievement significantly.Â